The Impact of Outdoor Learning Strategies Based on Islamic Religious Education Values on the Spiritual Intelligence of Early Childhood - Nurrohman Nurrohman; Farida Farida; Muhamad Sukri Situmeang; Mahamadaree Waeno; Mohd Ziaolhaq Qazi Zada (STAI Publisistik Thawalib Jakarta, 2025)
The spiritual intelligence of early childhood remains relatively low; thus, innovative, contextual, and experiential-based Islamic education strategies are required to support the spiritual, social, emotional, and physical development of children. This study aims to enhance children's spiritual abilities through interactive, contextually relevant outdoor Islamic Religious Education activities. The research employed an experimental design with observational data from 15 students. Data analysis was conducted using validity testing and t-tests in SPSS. The study's pretest results indicated low to moderate spiritual abilities in early childhood (average score 1.33–1.67), particularly in identifying religion, mimicking worship movements, reciting prayers, and distinguishing between good and bad behaviour. Observation of Outdoor Islamic Religious Education activities revealed improvement, with children displaying increased enthusiasm, greater orderliness in the mosque/musholla, greater independence during ablution, greater mimicry of prayer movements, and greater diligence in reading the Qur'an (average score 2–3, categorized as Moderate–Good). The posttest showed a significant improvement (average score 2.33–2.67), reflecting a better understanding of religious teachings, improved worship skills, and positive behaviour. Pearson validity test (r=0.977, p=0.000) and the t-test (p=0.000) confirmed that the data were valid and showed a significant increase in spiritual intelligence. In conclusion, outdoor Islamic Religious Education activities enhance religious understanding, worship skills, positive behaviour, and motor, coordination, and social skills, with statistically significant results